Role of Sustainability and Ethics in Fashion Design and Production in South America - Andrs, AgustÃn (International Journal of Fashion and Design, 2024)
Purpose: The aim of the study was to investigate the role of sustainability and ethics in fashion design and production. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Sustainability and ethics are pivotal in fashion design and production, shaping decisions across the supply chain. They drive innovation, reduce environmental impact, and ensure fair treatment of workers. Brands prioritizing sustainability and ethics meet consumer demands, fostering industry resilience and positive social impact. Integrating these principles is crucial for promoting a sustainable and responsible fashion industry. Unique Contribution to Theory, Practice and Policy: Sustainability theory, ethical fashion theory & systems theory may be used to anchor future studies on the role of sustainability and ethics in fashion design and production. Fashion designers and brands should prioritize sustainable materials, production processes, and supply chain practices. Governments and regulatory bodies play a critical role in establishing frameworks and incentives that encourage sustainable and ethical practices in the fashion industry.